TANGGUNG JAWAB BADAN PERTANAHAN NASIONAL TERHADAP PENERBITAN SERTIPIKAT HAK ATAS TANAH JIKA TERDAPAT BUKTI GIRIK (Studi Putusan Nomor 256/G/2019/PTUN-JKT) - Sheilfyra Chilvass (2022)
Land certificates In accordance with Article 32 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration states that Land Certificate must be considered correct in court as long as it cannot be proven otherwise by other evidence. In this case there's other proof of ownership in the form of girik. The type of research used is normative juridical, namely researching library materials or secondary materials with a statutory approach (statue approach) and a case approach (case approach). Sources of data were obtained from primary, secondary and tertiary legal materials processed using qualitative data analysis techniques with descriptive writing. The form of legal responsibility of the relevant official who issued the Decision Number 256/G/2019/PTUN-JKT is to revoke the Land Certificate that is above the Plaintiff's Girik in accordance with the decision issued by the State Administrative Court, the responsibility of the official authorized to ratify the land certificate is in the form of personal responsibility for maladministration. The actions of the State Administrative Court in deciding the cancellation of the Right to Use Certificate No. 38/Rawa Buaya and Certificate of Ownership No. 10218/Rawa Buaya are appropriate.